Cold War cultures : perspectives on Eastern and Western societies - Vowinckel, Annette; Payk, Marcus M.; Lindenberger, Thomas, 1955- (Berghahn Books, 2012)
The Cold War was not only about the imperial ambitions of the super powers, their military strategies, and antagonistic ideologies. It was also about conflicting worldviews and their correlates in the daily life of the societies involved. The term "Cold War Culture" is often used in a broad sense to describe media influences, social practices, and symbolic representations as they shape, and are shaped by, international relations. Yet, it remains in question whether -- or to what extent -- the Cold War Culture model can be applied to European societies, both in the East and the West. While every.